PENGARUH PUPUK ORGANIK CAIR URINE SAPI PLUS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L.) - Santoso, Untung; Rizali, Akhmad; Berutu, Yenni (EnviroScienteae, 2023)
Lettuce has great potential to be cultivated because it has a short harvest period, a wide open market, and a relatively stable price. The demand for lettuce also continues to increase, but the availability of lettuce stock is still limited. This causes the use of chemical fertilizers to increase. Continuous use of chemical fertilizers can damage soil fertility and the environment. One way that can be applied to support an environmentally friendly cultivation system is the use of liquid organic fertilizer plus cow urine. This liquid fertilizer is made from cow urine and additional ingredients in the form of spices and tobacco. Utilization of cow urine can help increase the economic value of livestock waste. In addition, this organic cow urine plus liquid organic fertilizer also contains nutrients that can help increase plant growth and yields. Additives such as spices and tobacco in fertilizers also help control pests on plants. The method in this study used a one-factor Randomized Block Design with p0 (0%), P1 (5%), P2 (15%), P3 (25%), P4 (35%), and P5 (45%). The results showed that liquid organic fertilizer plus cow urine had a significant effect on plant height, leaf width, number of leaves, and fresh weight of lettuce plants. The best concentration of organic cow urine plus fertilizer on the growth and yield of lettuce was found in treatment P1 (5%) with an average plant height of 9.22 cm, number of leaves of 14.75 cm, leaf width of 7.77, and fresh weight of 30.13 g.